Corporate disclosures by family firms - Ali, Ashiq; Chen, Tai-Yuan; Radhakrishnan, Suresh (Journal of Accounting and Economics, 2007)
Compared to non-family firms, family firms face less severe agency problems due to the separation of ownership and management, but more severe agency problems that arise between controlling and non-controlling shareholders. These characteristics of family firms affect their corporate disclosure practices. For S&P 500 firms, we show that family firms report better quality earnings, are more likely to warn for a given magnitude of bad news, but make fewer disclosures about their corporate governance practices. Consistent with family firms making better financial disclosures, we find that family firms have larger analyst following, more informative analysts’ forecasts, and smaller bid-ask spreads.